Peran Pemerintah Indonesia dalam Melindungi Hak TKI dari Praktik Underpayment di Hongkong - Donna Savira Larasati; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This thesis aims to analyze the role of the Indonesian government in protecting the rightsof migrant workers in Hongkong from underpayment practice in 2011 to 2017 by firstdescribing the description of underpayment practices in Hongkong, system andemployment policy of Hongkong, and the relationship between Indonesia and Hongkongin migrant workers. This thesis uses qualitative research methods with descriptive researchtypes and analyzed by collecting data collected from interviews, books, reports of NGOsand mass media. The range of research in this thesis is 2011 to 2017. To explain the role ofGovernment of Indonesia uses concept of public public, role theory and the concept ofhuman rights. The result of the research is the conclusion that Government of Indonesiaseeks to protect the right of Indonesia migrant workers in Hongkong from underpaymentpractice in form of policies, (i) enacted UU No. 39 tahun 2004, Keputusan Menakertrans98 tahun 2012, ratificate The International Convention on The Protection of The Rights ofAll Migrant Workers and Members of Their Families into UU No. 6 Tahun 2012,(ii) KJRIHongkong provides training to Indonesia migrant workers, blacklist employers andplacement agencies that are proven to be cheating, doing coordination with Ministry ofForeign Affairs and BNP2TKI, (iii) launched kredit usaha rakyat, (iv) doing MoU of laborprotection with Hongkong, and (v) coorporate with alliances of Indonesia migrant workersin Hongkong to monitor problems of Indonesia migrant workers.